Site indexes - The Editors, - (Nordic Archaeological Abstracts - NAA, 1982)
Sites are listed in two indexes. Medieval and later castles, churches, monasteries, and towns can be found in a separate index; these places are not included in the main index, where important find localities are listed. The relevant county, district, or region (according to the map) is always listed except when the paper deals with a larger area or with medieval castles, churches, etc. General surveys may be found under SURVEY in the Subject index. For the area outside the Nordic the name of the country is included, as are important find localities.